Pan-American Consortium of Multiple System Atrophy (Panmsa). a Pan-American Multicentre Cohort Study of Multiple System Atrophy - Chana-Cuevas, P (IOS Press, 2014)
Background: Multiple system atrophy (MSA) is an adult-onset and rapidly progressive, neurodegenerative condition that presents with autonomic dysfunction, parkinsonism, cerebellar ataxia and corticospinal deficits. Clinical, demographic and epidemiological data from different regions have provided valuable information concerning the natural history of MSA. There are no published data of Multiple System Atrophy (MSA) in Latin American countries. Objective: To describe clinical and epidemiological data of patients with possible MSA from seven referral movement disorders centers from Argentina, Chile, Mexico, Peru and United States. Methods: We conducted a retrospective, observational, cross-sectional Pan-American multicentre cohort study of MSA. Results: The sample was composed of 82 females and 77 men with the diagnosis of possible MSA with a mean age at onset of 65 ± 10 years. 67.29% of the individuals had a MSA-P variant with a mean age at onset of 61.47 ± 10.28 years, whereas the mean age at onset in the MSA-C patients was 57.44 ± 10.58 years. Interestingly, MSA-C-was more prevalent in Non-Caucasian (50-Mestizo and 2 Asian patients) than Caucasians (51.92% vs. 20.79%, p = 0.0001). Dysautonomic symptoms were present in 95.6% of the patients, parkinsonism in 85.5%, pyramidal signs in 25.8% and depression in 48.4% of the patients. Conclusions: Our epidemiological and clinical data appears to be similar to other Western international series, however, of note, the MSA-C phenotype was predominant in Non-Caucasians, more specifically the Mestizo population. This observation opens a new path to explore. Larger prospective epidemiologic studies in Latin America may provide valuable information concerning MSA in the region. © 2014-IOS Press and the authors.